23 A single centre experience of vascular access complications of transcatheter aortic valve replacement procedures. (October 2018) - Hennessey, B; Yearoo, I; Murphy, R; Teehan, S; Connolly, N; O'Connor, S; Kerr, B; Fitzpatrick, N; Brandon, L; Ali, M; Foley, B; Brennan, A; et al.
Abstract : Introduction: The rates of Transcatheter aortic valve implantation (TAVI) in comparison to surgical aortic valve replacement have steadily increased in the last ten years for treatment of severe symptomatic aortic stenosis in high-risk surgical candidates who would have otherwise been managed conservatively. Methods of vascular access management have also changed. Aim: The aim of our study was to assess the vascular access routes, closure device methods, individual failure rates of each device and the need for vascular surgical intervention for TAVI cases at our single centre in the Republic of Ireland. Methods: A retrospective data collection was conducted of elective TAVI procedures performed from December 2008 to February 2018 at a single centre in Dublin. All patients had severe symptomatic aortic stenosis as per international guidelines and were deemed unsuitable for surgical aortic valve replacement by the local heart team. The angiographic, echocardiographic, laboratory and radiographic data as well as access route, closure device type and mode of failure were recorded in a database. Results: A total of 129 patients (mean age 81.4±5.96 years of age, 51% female) had a TAVI implantation at our centre between December 2008 and February 2018.In 120 (93.02%) cases, the right femoral artery was the access site for the valve delivery sheath. In 117 (90.69%) of the total cases, the access was percutaneous. Four patients (3.10%) required vascular cut down, 6 cases (4.65%) required mini thoracotomy and 3 patients (2.32%) required mini sternotomy. Twenty -two patients (18.80%) experienced closure device failure, of which 18 patients (81.81%) had a leak, one patient (4.45%) had a dissection, one patient (4.45%) had an occlusion and two patients (9.09%) had a perforation. Of those twenty-two patients who had a closure device failure, 10 patients (45.45%) were treated successfully with pressure haemostasis and 4 cases (18.81%) were treated successful with balloon inflation. Seven patients (31.81%) required vascular surgery and one patient (4.45%) was treated by an interventional radiologist. In 111 of the cases, the closure device was recorded. 26 Proglide devices, 9 Vivasure devices and 76 Prostar devices were used. The Vivasure devices had a 55.55% failure rate. Five of the Proglide devices failed (19.23%) and 11(of the Prostar devices failed (14.47%). Of the 7 people requiring urgent vascular surgery, 5 has a failed Prostar device, one had a Vivasure device and in the last case the closure device was not documented. Conclusion: The majority of our cases were performed via the right Femoral artery with percutaneous access. While vascular closure device failures remain a clinically important complication of TAVI procedures, the need for surgical repair is low.